2018
DOI: 10.1186/s12862-018-1269-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple refugia from penultimate glaciations in East Asia demonstrated by phylogeography and ecological modelling of an insect pest

Abstract: BackgroundRefugial populations in Quaternary glaciations are critical to understanding the evolutionary history and climatic interactions of many extant species. Compared with the well-studied areas of Europe and Northern America, refugia of species in eastern Asia remain largely unknown. Here, we investigated the phylogeographic history of a globally important insect pest, the oriental fruit moth Grapholita molesta, in its native range of China.ResultsGenetic structure analyses unveiled three distinct groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 87 publications
2
29
0
Order By: Relevance
“…The Yungui Plateau (blue clade) fig wasps have also undergone significant expansion towards the end of the last glacial period. Expansions in ranges concurrent with the LGM are unusual (Qi et al, ; Qiu et al, ; Zhang et al, ), but have been reported for Taxus wallichiana (Liu et al, ), Osteomeles schwerinae (Wang, Chen, et al, ) and Grapholita molesta (Song et al, ) in this area. The Hengduan Mountains retained very few suitable habitats for F. tikoua during the LGM.…”
Section: Discussionmentioning
confidence: 93%
“…The Yungui Plateau (blue clade) fig wasps have also undergone significant expansion towards the end of the last glacial period. Expansions in ranges concurrent with the LGM are unusual (Qi et al, ; Qiu et al, ; Zhang et al, ), but have been reported for Taxus wallichiana (Liu et al, ), Osteomeles schwerinae (Wang, Chen, et al, ) and Grapholita molesta (Song et al, ) in this area. The Hengduan Mountains retained very few suitable habitats for F. tikoua during the LGM.…”
Section: Discussionmentioning
confidence: 93%
“…The phylogenetic tree showed that the genotypes from the Sichuan Basin (Sichuang, Chongqing) were closest to those of P. taeda and were followed by other clades, suggesting that the Sichuan Basin is the geographic origin of masson pine. The Sichuan Basin was one of several glacial refuges for many species during the last Pleistocene glaciations [28,29], which may have rescued the masson pine from an extinction event. The masson pine gradually migrated to the Guizhou Plateau after the end of the glacial epoch and gradually adapted to the plateau habitat.…”
Section: Population Structure Of the P Massoniana Germplasmmentioning
confidence: 99%
“…For example, in Europe, many studies have shown how the persistence of populations in separate glacial refugia (e.g., the Iberian, Italian, and Balkan peninsulas, the Caucasus region, North Africa, and microrefugia in the Alps) during the Quaternary climatic oscillations promoted genetic diversity in contemporary populations (Andersen, Havill, Caccone, & Elkinton, ; Habel, Lens, Rodder, & Schmitt, ; Huck, Buedel, & Schmitt, ; Niedzialkowska et al, ; von Reumont, Struwe, Schwarzer, & Misof, ; Rofes et al, ; Schmitt, ; Schmitt & Müller, ; Sim, Hall, Jex, Hegel, & Coltman, ; Stolting et al, ; Torroni et al, ). For outbreaking species, reconstructing the biogeographical history of the species can help to determine the factors that might be promoting their outbreak (e.g., Moyal et al, ; Song et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%